Alzheimer's amyloid-beta intermediates generated using polymer-nanodiscs. Issue 91 (31st October 2018) - Sahoo, Bikash R.; Genjo, Takuya; Bekier, Michael; Cox, Sarah J.; Stoddard, Andrea K.; Ivanova, Magdalena; Yasuhara, Kazuma; Fierke, Carol A.; Wang, Yanzhuang; Ramamoorthy, Ayyalusamy
Abstract : Polymethacrylate-copolymer (PMA) encased lipid-nanodiscs modulate Aβ1–40 aggregation and neurotoxicity. Abstract : Polymethacrylate-copolymer (PMA) encased lipid-nanodiscs (∼10 nm) and macro-nanodiscs (>15 nm) are used to study Aβ1–40 aggregation. We demonstrate that PMA-nanodiscs form a ternary association with Aβ and regulate its aggregation kinetics by trapping intermediates. Results demonstrating the reduced neurotoxicity of nanodisc-bound Aβ oligomers are also reported.